Screening method of aluminum oxide raw material for glass substrate
By conducting physical and chemical performance testing of alumina raw materials and melting test of glass material, the optimal alumina raw materials were selected, which solved the problems of singleness and tight supply in the existing technology, and achieved an efficient and economical glass substrate. Production.
Patent Information
- Application Number
- CN202411521643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-25
AI Technical Summary
It is difficult for the prior art to accurately screen out high-quality alumina raw materials suitable for glass substrate production, resulting in problems such as single raw materials, tight supply and increased production costs.
By conducting physical and chemical performance testing of the alumina raw materials to be screened, alumina raw materials that meet the usage standards were screened, and they were prepared into glass frit squares for melting and thermal performance testing. The final comprehensive results were used to screen out the optimal alumina raw materials. .
Accurate screening of alumina raw materials is achieved, the use of α alumina is ensured, production efficiency is improved, costs are reduced, and risks brought by a single supplier are avoided.
Smart Images

Figure CN119510485A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass production, and in particular to a method for screening aluminum oxide raw materials for glass substrates. Background Art
[0002] With the vigorous development of the liquid crystal panel industry at home and abroad, domestic liquid crystal panel display technology has also developed rapidly. Liquid crystal substrate glass is the key glass material for the front and back of thin film transistor liquid crystal displays. As an important component of the panel, it is also particularly important. In the production of substrate glass, various raw materials involved in the ingredients play an important role, especially alumina. As we all know, alumina has different structural crystal forms, which are divided into α-alumina, β-alumina and γ-alumina. For alumina with different crystal structures, structurally, the oxygen ions of α-alumina are hexagonally closely packed, and Al 3+ The oxygen ions are symmetrically distributed in the octahedral coordination center surrounded by oxygen ions, and the lattice energy is very large, so the melting point and boiling point are very high; in the structure of γ-alumina, the oxygen ions are approximately face-centered and closely packed. 3+ Irregularly distributed in the octahedral and tetrahedral voids surrounded by oxygen ions. In terms of properties, α-alumina is insoluble in water and acid, has good chemical stability, high purity, uniform particle size distribution, low specific surface area, and is inert to high temperatures; β-alumina is actually not aluminum oxide, but a composite oxide of aluminum oxide and sodium oxide, and its morphology is difficult to control; γ-alumina is insoluble in water, but soluble in strong acid or strong alkali solutions. It is a porous substance with an internal surface area of hundreds of square meters per gram, high activity, and strong adsorption capacity. Therefore, α-alumina is often used as the raw material for the production of TFT glass substrates. However, the appearance of α-alumina, β-alumina, and γ-alumina is very similar, and it is difficult to judge by simple appearance. Therefore, it is important to choose alumina raw materials suitable for glass production. At the same time, alumina is a high hardness compound with a melting point of 2054°C and a boiling point of 2980°C. It is an ionic crystal that can be ionized at high temperatures and is often used to make refractory materials. Therefore, in the production of glass substrates, it is very important to screen out high-quality alumina raw materials suitable for glass ingredients.
[0003] In the past production of glass substrates, alumina commonly used by similar glass substrate manufacturers was used as raw material. There was a lack of selectivity for the same raw material from different manufacturers, which not only caused the uniformity of the alumina raw material, causing certain economic or supply problems that affected production, but also it was difficult to ensure that when developing raw materials from new suppliers, there would be no mixing of alumina with different crystal structures. Therefore, how to screen out more alumina raw materials that meet the use requirements without affecting the normal kiln production process is one of the problems that need to be solved in current production. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for screening alumina raw materials for glass substrates, which can accurately screen out α alumina with the best use effect, has good effectiveness and accuracy, and reduces the impact on the actual production process.
[0005] The technical solution of the present invention is:
[0006] A method for screening aluminum oxide raw materials for glass substrates comprises the following steps:
[0007] S1 performs physical and chemical property tests on the alumina raw materials to be screened, and screens out the alumina raw materials that meet the use standards;
[0008] S2 prepares the screened alumina raw materials into glass frit;
[0009] S3 melts the glass material into a glass frit, and counts the number of bubbles per kilogram and observes the transparency of the glass frit;
[0010] S4 tests the thermal properties of glass frit;
[0011] S5 combines the above statistics, observations and test results to select the best aluminum oxide raw material for glass substrates.
[0012] Preferably, in step S1, the physical and chemical properties test items and the corresponding usage standards are: moisture content ≤0.2wt.%, ignition loss ≤0.2wt.%, Al2O3 content ≥99.8wt.%, alkali metal content ≤0.05wt.%, Fe2O3 content ≤0.01wt.%, SO3 content ≤0.1wt.%, trace element content ≤0.01wt.%, component content with a particle size of 0.15-0.25mm ≤0.1wt.%, component content with a particle size of 0.106-0.15mm ≤3wt.%, and component content with a particle size less than 0.045mm ≤30wt.%.
[0013] Preferably, in step S3, the method for melting the glass frit is as follows: after heating the glass material to 1630° C. and keeping the temperature, the molten glass liquid is taken out for molding, and annealing and cooling are performed to obtain the glass frit.
[0014] Preferably, the process of heating the glass material to 1630°C is as follows: the temperature is raised from room temperature to 1000°C, then raised to 1560°C after 60 minutes, and kept warm for 3 hours; then raised to 1600°C after 5 minutes, and kept warm for 2 hours; then raised to 1630°C after 5 minutes, and kept warm for 1.5 hours.
[0015] Preferably, the annealing cooling process is: annealing cooling at 730° C. for 1 hour.
[0016] When the material is heated, it is mainly a solid phase reaction at first, with a large amount of gas escaping, and the material gradually changes from solid to liquid. As the solid phase continues to transform into the liquid phase, the liquid phase continues to expand, and the basic reaction of the material is basically completed, forming an opaque sinter composed of silicate and free silicon dioxide, and the silicate formation process is basically completed.
[0017] Preferably, in step S3, when observing the permeability of the glass frit, if no unmelted matter is found in the glass frit, the permeability of the glass frit is good, otherwise, the permeability is poor.
[0018] Preferably, in step S4, the thermal properties include the thermal expansion coefficient, annealing point and strain point of the glass.
[0019] Preferably, the process further includes step S6: observing and analyzing the melting bubbles of the glass prepared in step S2 at 1650°C: dynamically observing the melting process of the glass by a high-temperature imaging observation system, collecting pictures of the melting process of the glass and analyzing and processing the dynamic changes of the bubbles.
[0020] Preferably, the glass frit is placed in a quartz crucible and placed in a high-temperature dynamic observation furnace of a high-temperature imaging observation system, and the glass frit is melted according to the following procedure: first, the temperature is increased to 500°C at a rate of 20°C / min, then the temperature is increased to 1400°C at a rate of 10°C / min, and then the temperature is increased to 1600°C at a rate of 5°C / min, and the temperature is kept at 1600°C for 3 hours.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention designs a method for screening alumina raw materials for glass substrates, which can accurately distinguish alumina with different crystal structures, ensure the use of α alumina, and the method is simple, highly operable, does not require a large amount of time and resources, and has good effectiveness and accuracy. The screening method of the present invention can accurately detect the compatibility of alumina with other glass raw materials, and at the same time, it does not directly affect the kiln process. By using the method of approximate process production, it can more directly reflect the influence of a single variable alumina in the raw materials on the production of glass materials, and then by selecting alumina with the best reaction effect for actual production, it can reduce the impact on the actual production process, reduce costs, and avoid the risks of cost and supply timeliness brought by a single supplier. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the result of observing the transparency of the glass frit made from the α-alumina raw material of Manufacturer A in Example 1 of the present invention.
[0024] Figure 2 This is the result of observing the transparency of the glass frit made from the β-alumina raw material of Manufacturer B in Example 1 of the present invention.
[0025] Figure 3 This is the result of observing the transparency of the glass frit made from the γ-alumina raw material of Manufacturer C in Example 1 of the present invention.
[0026] Figure 4 This is a photograph of the mirror cleanliness of the glass material prepared from the α-alumina raw material of Manufacturer A in Example 1 of the present invention during the melting process.
[0027] Figure 5 This is a photograph of the mirror cleanliness of the glass material prepared from the β-alumina raw material of Manufacturer B in Example 1 of the present invention during the melting process.
[0028] Figure 6 This is a photograph of the mirror cleanliness of the glass material prepared from the γ-alumina raw material of Manufacturer C in Example 1 of the present invention during the melting process.
[0029] Figure 7 This is a photo of a glass substrate produced after the α-alumina raw material from Manufacturer A in Example 1 of the present invention is used in the production line.
[0030] Figure 8 This is a photo of a glass substrate produced after the β-alumina raw material from Manufacturer B in Example 1 of the present invention is used in the production line.
[0031] Fig. 9 This is a photo of a glass substrate produced after the γ-alumina raw material from Manufacturer C in Example 1 of the present invention is used in the production line. DETAILED DESCRIPTION
[0032] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0033] Example 1
[0034] The α alumina raw material from manufacturer A, the β alumina raw material from manufacturer B, and the γ alumina raw material from manufacturer C are selected respectively, and the optimal alumina raw material is screened out by the screening method of the present invention. Specifically, the following steps are included:
[0035] S1 tests the physical and chemical properties of three alumina raw materials
[0036] The test items and methods are as follows:
[0037] 1) Moisture content detection: Dry the weighing bottle to constant weight, then weigh about 5g (accurate to 0.0001g) of alumina raw material sample into the weighing bottle, cover the bottle cap with a small gap, and dry it at 300℃ to constant weight. The moisture content in the raw material can be calculated based on the weight loss before and after.
[0038] 2) Loss on ignition: Dry the platinum crucible to constant weight, pour the sample after moisture content testing directly into the platinum crucible, and dry it at 1000°C to constant weight. The weight loss before and after is the loss on ignition;
[0039] 3) Component detection: weigh about 1g (accurate to 0.0001g) of the dried sample into a polytetrafluoroethylene beaker, add 20mL of HCl (1+1), stir well, place in an electric furnace for low-temperature heating to fully leaching, then cool to room temperature, filter into 100mL volumetric flasks; pay attention to washing the precipitate fully and not splashing the washing liquid, dilute to 100mL with pure water, shake well, and obtain the test solution; prepare standard solutions of different concentrations, and use inductively coupled plasma emission spectrometer to detect the content of each component;
[0040] 4) Particle size detection: Use a vibrating screen machine and refer to "GB / T21524-2008 Determination of particle size in inorganic chemical products - Sieving method" to select a sieve with the particle size required by the standard for screening.
[0041] The physical and chemical properties test results of the three selected alumina raw materials are shown in Table 1:
[0042] Table 1 Physical and chemical properties test results of three alumina raw materials
[0043]
[0044] According to the test results in Table 1, the α alumina raw materials from manufacturer A and the β alumina raw materials from manufacturer B that meet the use standards are screened out for the next step of screening; however, in order to verify whether the use standards of the physical and chemical properties of the alumina raw materials set by the present invention are accurate, the γ alumina raw materials from manufacturer C are also screened in the next step.
[0045] S2 prepares the three aluminum oxide raw materials into glass frits, and the glass frits are shown in Table 2:
[0046] Table 2 Glass frit
[0047] Ingredients <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[B 2 THE 3 ]]> MgO CaO SrO Content / wt.% 62 17 9.5 2 6.5 3 raw materials Quartz sand Alumina Boron Oxide Magnesium oxide Calcium carbonate Strontium carbonate
[0048] The raw materials in Table 2, except alumina, were purchased from the same manufacturer.
[0049] S3 melts the glass frit into glass blocks, and counts the number of bubbles per kilogram and observes the transparency of the glass blocks
[0050] (1) Prepare Mettler ME2002 precision balance, Yixing Wanshi JGMT-8 / 300 silicon aluminum rod lifting furnace (melting temperature can reach 1750℃), and pure brass mold;
[0051] (2) Weigh the required raw materials according to the glass frit formula in Table 2, with a total weight of 600 g;
[0052] (3) The silicon aluminum rod lifting furnace is set according to the melting program: the temperature is raised from room temperature to 1000°C, then raised to 1560°C after 60 minutes, and kept warm for 3 hours; then raised to 1600°C after 5 minutes, and kept warm for 2 hours; then raised to 1630°C after 5 minutes, and kept warm for 1.5 hours. After the end of the insulation, the melting is completed, the molten glass liquid is taken out and formed on a brass mold, and then kept warm at 730°C for 1 hour for annealing and cooling;
[0053] (4) Take out the cooled glass frit, count the number of bubbles in the glass frit made of the three alumina raw materials, weigh the glass frit, calculate the number of bubbles per kilogram, and observe the permeability of the glass frit. The results are as follows: Figure 1-3 As shown in the figure, no unmelted material was found in the three glass frits. The statistical and observation results are shown in Table 3:
[0054] Table 3 Bubble count per kilogram and permeability of three glass frits
[0055]
[0056] It can be seen from Table 3 that the number of bubbles per kilogram of the α alumina raw material of manufacturer A is much lower than that of the β alumina raw material of manufacturer B and the γ alumina raw material of manufacturer C.
[0057] S4 Tests the Thermal Properties of Glass Frit
[0058] According to ASTM E-228 Test method for linear thermal expansion of solid materials using push rod dilatometer, the thermal expansion coefficient of glass at 30-380°C is measured in units of 10 -7 / ℃; refer to "ASTM C-336 Standard Test Method for Annealing Point and Strain Point of Glass by Fiber Elongation", use a three-point tester to measure the annealing point and strain point of the glass, the unit is ℃.
[0059] The thermal performance test results of the three glass frits are shown in Table 4:
[0060] Table 4 Thermal performance test results of three glass frits
[0061]
[0062] It can be seen from Table 4 that the glass frit melted from α-alumina raw materials not only has higher annealing point and strain point than β-alumina raw materials and γ-alumina raw materials, but also has lower expansion coefficient than β-alumina raw materials and γ-alumina raw materials. For glass substrates, this will reduce the degree to which the glass substrate is affected by temperature changes during the customer's process stage, reducing thermal expansion and deformation.
[0063] S5 Observation and analysis of melt bubbles at 1650℃ on glass frit
[0064] The melting process of the glass frit was dynamically observed by the high-temperature imaging observation system produced by the Czech GLASSSERVICE company. According to Table 2, a glass frit with a total weight of 50g was prepared, placed in a quartz crucible, and placed in a high-temperature dynamic observation furnace. The glass frit was melted according to the following procedure: first, the temperature was increased to 500℃ at a rate of 20℃ / min, then to 1400℃ at a rate of 10℃ / min, and then to 1600℃ at a rate of 5℃ / min, and kept at 1600℃ for 3h; the pictures of the melting process were collected and the dynamic changes of bubbles were analyzed and processed to better compare the mirror cleanliness of the three glass frits during the melting process. The comparison results are shown in Figure 2. Figure 4-6 As shown in Table 5:
[0065] Table 5 Mirror cleanliness of three glass materials during melting process
[0066]
[0067] By comparison Figure 4-6 From the mirror cleanliness of the three different materials in the melting process in Table 5, it can be seen that the mirror surface of the glass material prepared from the α-alumina raw material of Manufacturer A is cleaner, which is better than the glass material prepared from the β-alumina raw material of Manufacturer B and the γ-alumina raw material of Manufacturer C.
[0068] S6
[0069] Based on the above statistics, observations and test results, it can be concluded that the α-alumina raw material produced by Manufacturer A is the best and can be used as the alumina raw material for glass substrates.
[0070] Finally, by using the above three alumina raw materials in the glass substrate production line and comparing the basic stripe conditions of the production line glass, it is verified that the α alumina raw material of manufacturer A selected in this embodiment does have the best performance. The stripe conditions of the glass substrates produced after the three alumina raw materials are used in the production line are shown in Table 6:
[0071] Table 6 Stripe situation of glass substrate produced by three kinds of aluminum oxide raw materials after production line
[0072] Alumina raw materials Alpha Alumina Raw Materials β-alumina raw materials Gamma Alumina Raw Materials Stripe Level Stripes are not obvious, normal Obvious vertical stripes, level 5 Vertical and parabolic stripes are obvious, level 6 Qualified or not qualified Failure Failure
[0073] Among them, the glass substrate with no obvious stripes is qualified; the stripes ≥ 4 are unqualified. At the same time, the photos of the glass substrates produced after the three types of alumina raw materials are used in the production line are as follows Figure 7-9 As shown in Table 6 and Figure 7-9It can be seen from the comparison that the use effect of the α alumina raw material of manufacturer A is indeed better than the β alumina raw material of manufacturer B and the γ alumina raw material of manufacturer C, which is consistent with the conclusion drawn in Example 1, verifying the feasibility and accuracy of the screening method of the present invention.
[0074] In summary, the screening method of the present invention meets the actual use requirements, and the operation process is simple and does not require a lot of time and resources.
Claims
1. A method for screening alumina raw materials for glass substrates, characterized in that: The following steps are involved: S1 performs physical and chemical property tests on the alumina raw materials to be screened, and screens out the alumina raw materials that meet the use standards; S2 prepares the screened alumina raw materials into glass frit; S3 melts the glass material into a glass frit, and counts the number of bubbles per kilogram and observes the transparency of the glass frit; S4 tests the thermal properties of glass frit; S5 combines the above statistics, observations and test results to select the best aluminum oxide raw material for glass substrates.
2. The method for selecting alumina raw materials for glass substrates according to claim 1, wherein: In step S1, the physical and chemical properties test items and the corresponding use standards are: moisture content ≤0.2wt.%, ignition loss ≤0.2wt.%, Al2O3 content ≥99.8wt.%, alkali metal content ≤0.05wt.%, Fe2O3 content ≤0.01wt.%, SO3 content ≤0.1wt.%, trace element content ≤0.01wt.%, component content with a particle size of 0.15-0.25mm ≤0.1wt.%, component content with a particle size of 0.106-0.15mm ≤3wt.%, and component content with a particle size less than 0.045mm ≤30wt.%.
3. The method for selecting alumina raw materials for glass substrates according to claim 1, wherein: In step S3, the melting method of the glass frit is as follows: after heating the glass material to 1630° C. and keeping the temperature, the molten glass liquid is taken out for molding, and annealing and cooling are performed to obtain the glass frit.
4. The method for selecting alumina raw materials for glass substrates according to claim 3, wherein: The process of heating the glass material to 1630°C is as follows: the temperature is raised from room temperature to 1000°C, then raised to 1560°C after 60 minutes, and kept warm for 3 hours; then raised to 1600°C after 5 minutes, and kept warm for 2 hours; then raised to 1630°C after 5 minutes, and kept warm for 1.5 hours.
5. The method for selecting alumina raw materials for glass substrates according to claim 3, wherein: The annealing cooling process is: annealing cooling at 730°C for 1 hour.
6. The method for selecting alumina raw materials for glass substrates according to claim 1, wherein: In step S3, when observing the permeability of the glass frit, if no unmelted matter is found in the glass frit, the permeability of the glass frit is good, otherwise, the permeability is poor.
7. The method for selecting alumina raw materials for glass substrates according to claim 1, wherein: In step S4, the thermal properties include the thermal expansion coefficient, annealing point and strain point of the glass.
8. The method for selecting alumina raw materials for glass substrates according to claim 1, wherein: The method also includes step S6: observing and analyzing the melting bubbles of the glass material prepared in step S2 at 1650°C: dynamically observing the melting process of the glass material through a high-temperature imaging observation system, collecting pictures of the melting process of the glass material, and analyzing and processing the dynamic changes of the bubbles.
9. The method for selecting alumina raw materials for glass substrates according to claim 8, wherein: The glass frit was placed in a quartz crucible and placed in a high-temperature dynamic observation furnace of a high-temperature imaging observation system. The glass frit was melted according to the following procedure: first, the temperature was raised to 500°C at a rate of 20°C / min, then to 1400°C at a rate of 10°C / min, then to 1600°C at a rate of 5°C / min, and kept at 1600°C for 3 hours.